Heavy metal adsorption filler as well as preparation method and application thereof

By preparing heavy metal adsorption packing material through mixed pyrolysis of biomass and attapulgite soil and the attachment of sulfate-reducing bacteria, the problems of complex processes and high costs in existing technologies are solved, and efficient and stable heavy metal adsorption and recovery effects are achieved.

CN121372374APending Publication Date: 2026-01-23CHINALCO ENVIRONMENTAL PROTECTION & ENERGY CONSERVATION GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511701597.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-19
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing heavy metal adsorbents have complex preparation processes and high costs, and lack the broad-spectrum and stability of bioremediation. Microbial adsorbents are prone to failure under long-term immersion in groundwater.

Method used

A heavy metal adsorption packing material with high mechanical strength and broad-spectrum adsorption performance was prepared by mixing and pressing biomass, attapulgite clay and pore-forming agent, followed by anaerobic pyrolysis.

Benefits of technology

It achieves stable and reliable heavy metal adsorption and recovery in dynamic environments, has high mechanical strength and broad spectrum, avoids the failure of microorganisms under scouring, simplifies the preparation process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of anhydrous treatment, in particular to a heavy metal adsorption filler as well as a preparation method and application thereof. The preparation method comprises the following steps: firstly, mixing biomass, attapulgite, a pore-forming agent and water, and performing compression molding to obtain raw material balls; the raw material balls are sequentially subjected to first drying and anoxic pyrolysis, and filler balls are obtained; and soaking the filler balls in a sulfate reducing bacteria solution, and sequentially carrying out biofilm formation and secondary drying to obtain the heavy metal adsorption filler. The heavy metal adsorption filler obtained by the method can effectively adsorb heavy metals, has higher mechanical strength and is suitable for repairing underground water.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of anhydrous processing technology, in particular to a heavy metal adsorption filler and a preparation method and application thereof. BACKGROUND

[0002] Groundwater heavy metal pollution remediation of industrial and mining land is a major challenge in the field of environmental remediation. Mining, metallurgy and chemical activities lead to the continuous invasion of aquifer by heavy metals such as cadmium (Cd), lead (Pb) and zinc (Zn) through leachate and tailings leaching, forming a large range of pollution plume. Adsorption is a commonly used method for groundwater heavy metal pollution remediation. In the prior art, patent CN120328675A repairs heavy metal contaminated groundwater by a double-layer slow-release composite repair agent, achieving the removal of lead; patent CN119425613A loads layered double hydroxide (intercalated with chelating agent) onto biochar to prepare an adsorbent, achieving the removal of heavy metals such as lead and cadmium; patent CN119281296A synthesizes nano iron and copper particles on biochar, efficiently reducing hexavalent chromium. Although the above adsorbents based on physicochemical reactions can remove heavy metals from groundwater, the preparation process of the above adsorbents involves double-layer coating technology, chelating agent intercalation, nitrogen protection synthesis and other steps, which are complex and costly. At the same time, pure physicochemical engineering lacks the broad-spectrum and sustainability of biological remediation. Patent CN118652880A introduces microorganisms into the adsorption process to precipitate heavy metals by producing sulfides by microorganisms, but PVA-sodium alginate gel has low mechanical strength and is easily damaged under long-term soaking and flushing of groundwater. How to provide an efficient and stable heavy metal adsorbent is a problem to be solved at present. SUMMARY

[0003] The present application provides a heavy metal adsorption filler and a preparation method and application thereof, which can effectively adsorb heavy metals and has high mechanical strength, suitable for groundwater remediation.

[0004] The present application provides a preparation method of a heavy metal adsorption filler, comprising the following steps: mixing biomass, attapulgite, pore-forming agent and water, and pressing to form green balls, subjecting the green balls to first drying and anaerobic pyrolysis in sequence to obtain filler balls, immersing the filler balls in a sulfate-reducing bacteria solution, and sequentially performing biological membrane formation and second drying to obtain a heavy metal adsorption filler.

[0005] Optionally, the biomass is at least one of straw powder, wood chips, rice husk powder and bamboo pole powder, and the particle size of the biomass is 20-40 mesh.

[0006] Optionally, the attapulgite has a particle size of 100-150 mesh.

[0007] Optionally, the pore-forming agent is at least one of sodium bicarbonate and calcium carbonate.

[0008] Optionally, the biomass is 100 parts, the attapulgite is 50-65 parts, the pore-forming agent is 3-8 parts, and the water is 30-40 parts by mass.

[0009] Optionally, the device for press forming is a roller-type ball press, and the linear specific pressure is 3-5 kN / cm.

[0010] Optionally, the air process coefficient of the anoxic pyrolysis is less than 1, the temperature of the anoxic pyrolysis is 500-600℃, and the time of the anoxic pyrolysis is 4-6 h.

[0011] Optionally, the absorbance of the sulfate-reducing bacteria solution at 600 nm is greater than or equal to 0.8.

[0012] Optionally, the preparation method further comprises adding 0.05-0.1 wt% ferrous sulfate to the sulfate-reducing bacteria solution.

[0013] Optionally, the temperature for biofilm formation is 30-35℃, and the time is 7-10 days.

[0014] Optionally, the temperature for the second drying is 30-40℃, and the degree of the second drying is to reduce the water content to less than 5 wt%.

[0015] The present application also provides a heavy metal adsorption filler prepared by the preparation method of any one of the above technical solutions.

[0016] The present application also provides the application of the heavy metal adsorption filler of the above technical solution in the removal of heavy metals in groundwater.

[0017] Optionally, the application comprises soaking the heavy metal adsorption filler in an activation nutrient solution for 23-30 h for activation, and then placing it in a groundwater remediation well for heavy metal removal. The activation nutrient solution is a mixed aqueous solution of sodium lactate, ammonium sulfate, and potassium dihydrogen sulfate, wherein the concentration of sodium lactate is 0.8-1.2 g / L, the concentration of ammonium sulfate is 0.15-0.25 g / L, and the concentration of potassium dihydrogen phosphate is 0.03-0.07 g / L.

[0018] Compared with the prior art, the present application has the following beneficial effects: The application converts the mixture of biomass and mineral binder into regular filler with good adsorption performance and mechanical strength through the simple process of external combustion type stacking stewing, and then the obtained heavy metal adsorption filler with high mechanical strength is stable and reliable in dynamic environment, so that the adsorption enrichment and recovery of heavy metals in groundwater can be realized. In addition, the application uses S 2- The application generates insoluble metal sulfide precipitate with most cationic heavy metals, realizes the removal of various heavy metals in groundwater, has broad spectrum, and loads the microorganism on the filler, avoids the washing failure of the microorganism, and has high stability. DETAILED DESCRIPTION

[0019] The application will be described below through specific embodiments, and those skilled in the art can understand that the specific embodiments below are only for illustrative purposes, and do not limit the scope of the application in any way. In addition, in the following embodiments, unless otherwise specified, the reagents and equipment used are commercially available. If the specific treatment conditions and methods are not explicitly described in the following embodiments, the conditions and methods known in the art can be used for treatment.

[0020] The application provides a preparation method of heavy metal adsorption filler, which comprises the following steps: The biomass, attapulgite, pore-forming agent and water are mixed and compression molded to obtain green balls, The green balls are sequentially subjected to first drying and anoxic pyrolysis to obtain filler balls, The filler balls are soaked in a sulfate-reducing bacteria solution, and are sequentially subjected to biological membrane hanging and second drying to obtain heavy metal adsorption filler.

[0021] The present application uses attapulgite as a binder, mixes with biomass, pore-forming agent and water, is pressed into a molding, obtains green balls, and then is subjected to first drying and anaerobic pyrolysis. Under the condition of oxygen deficiency (i.e. anaerobic), biomass pyrolysis forms abundant pore structure. At the same time, due to the anaerobic condition, carbonization and slight activation are combined, the functional groups such as hydroxyl and carboxyl of biomass are retained, the complexing ability of the filler to heavy metals is improved, and the oxidation of trace oxygen can further etch the carbon skeleton to form more abundant pores. At the same time, anaerobic pyrolysis is also helpful for sintering and phase change of attapulgite to form ceramic mineral phases (such as iron oxide and silicate), improve the hardness and wear resistance of the material, and the mineral phases have catalytic or adsorption activity, which is beneficial to further improve the removal effect of heavy metals. The mineral phase and biochar have a synergistic effect on Cd, Pb, Zn, Cu and other heavy metals, and the raw materials are all natural minerals and biomass, without toxic additives and leaching risk (i.e. no release of toxic and harmful substances). The filler balls obtained by combining pressing and anaerobic pyrolysis have excellent mechanical properties, are stable and reliable in a dynamic environment, and are suitable for groundwater remediation. Moreover, the heavy metal adsorption material provided by the present application can be stored for a long time after packaging, and only needs to be activated simply when used on site, which is convenient for engineering application and easy to scale up and commercialize.

[0022] First, the biomass, attapulgite, pore-forming agent and water are mixed, and then pressed into a molding to obtain green balls.

[0023] In some embodiments of the present application, the biomass is waste gas microorganism, and specifically can include at least one of straw powder, sawdust, rice husk powder and bamboo pole powder. The surface of the biomass is rich in mineral components and functional groups, and naturally has ion exchange and complexing sites, which have specific attraction to heavy metals. In the present application, the biomass plays a role of skeleton.

[0024] In some embodiments of the present application, the particle size of the biomass is 20-40 mesh, i.e. can pass through a 20-40 mesh sieve, and specifically can be 20 mesh, 40 mesh, etc.

[0025] In some embodiments of the present application, the particle size of the attapulgite is 100-150 mesh, i.e. can pass through a 100-150 mesh sieve, and specifically can be 100 mesh, 120 mesh, 150 mesh, etc. In the present application, the attapulgite plays a role of filler and binder. The fine particles can be filled into the pores between the medium-coarse biomass particles, increase the density of the mixture, and improve the initial strength of the green balls.

[0026] In some embodiments of the present application, the pore-forming agent is at least one of sodium bicarbonate and calcium carbonate. In the present application, the pore-forming agent is decomposed by heat, and the generated CO2 escapes from the inside of the material to the outside, thereby leaving a large number of micropores in the filler after solidification.

[0027] In some embodiments of the present application, the biomass is 100 parts by mass, the attapulgite is 50-65 parts, the pore-forming agent is 3-8 parts, and the water is 30-40 parts. In the present application, the above-mentioned ratio of attapulgite ensures that the obtained green balls have high strength, while ensuring that the pores in the biomass are unobstructed, avoiding excessive densification; the above-mentioned amount of pore-forming agent ensures good pore-forming effect, while avoiding excessively large pores that can reduce the strength of the final obtained filler; and the above-mentioned amount of water further ensures the plasticity of the green balls, so that the mixture has good processing performance.

[0028] In some embodiments of the present application, based on 100 parts by mass of biomass, the amount of attapulgite can be 50 parts, 51 parts, 55 parts, 58 parts, 60 parts, etc.; the amount of pore-forming agent can be 3 parts, 5 parts, 6 parts, 7 parts, 8 parts, etc.; and the amount of water can be 30 parts, 34 parts, 37 parts, 40 parts, etc.

[0029] The present application does not have special limitations on the specific way of mixing the biomass, attapulgite, pore-forming agent and water, and the four components can be mixed uniformly; in the examples of the present application, the biomass, attapulgite and pore-forming agent are first mixed uniformly, and then water is added and mixed uniformly, and the obtained mixture is a clay material.

[0030] In some embodiments of the present application, the equipment for press forming is a roller-type ball press, and the linear specific pressure is 3-5 kN / cm, specifically 3 kN / cm, 4 kN / cm, 5 kN / cm, etc. Under the above-mentioned specific linear specific pressure, the particles are tightly compacted, ensuring the initial strength of the filler balls; the tight contact between the biomass and attapulgite particles allows more complete sintering and bonding of the mineral phase during subsequent pyrolysis; and a pressure exceeding this range can result in excessively dense green balls, which is not conducive to gas escape and affects pore development.

[0031] In some embodiments of the present application, the particle size of the green balls is 35-45 mm, specifically 35 mm, 40 mm, 45 mm, etc.

[0032] After obtaining the green balls, the present application sequentially performs first drying and anaerobic pyrolysis on the green balls to obtain filler balls.

[0033] In some embodiments of the present application, the first drying is natural air drying, and the first drying time is 45-50 h, specifically 45 h, 48 h, 50 h, etc. In the present application, the first drying can shape the green balls, and at the same time save energy without subsequent anaerobic pyrolysis. If the green balls are directly subjected to anaerobic pyrolysis without first drying, the phenomenon of collapse is prone to occur. In addition, the breakage rate of the green balls obtained after the first drying is less than 5% when the green balls are dropped freely from a height of 0.5 m. Natural air drying is a slow and uniform dehydration process, which can gradually remove the free water in the green balls. If the green balls do not go through this step and are directly subjected to high-temperature pyrolysis, the internal moisture will instantaneously vaporize due to rapid heating, which is easy to cause the structure of the green balls to collapse.

[0034] In some embodiments of the present application, the air process coefficient of the anaerobic pyrolysis is less than 1, specifically 0.9, 0.8, 0.7, etc.; the temperature of the anaerobic pyrolysis is 500-600℃, specifically 500℃, 550℃, 600℃, etc.; and the time of the anaerobic pyrolysis is 4-6 h, specifically 4 h, 5 h, 6 h, etc. The equipment for the anaerobic pyrolysis in the present application is not particularly limited, and can meet the above conditions. In the embodiments of the present application, the anaerobic pyrolysis is carried out in an industrial kiln.

[0035] After obtaining the filler balls, the filler balls are soaked in a sulfate-reducing bacteria solution in the present application, and biological membrane formation and second drying are sequentially carried out to obtain heavy metal adsorption fillers. After biological membrane formation and second drying of the filler balls in the present application, dry heavy metal adsorption fillers are obtained. The fillers can be packaged, stored, and activated simply when needed, and then used in engineering applications.

[0036] In some embodiments of the present application, the absorbance of the sulfate-reducing bacteria solution at 600 nm is ≥0.8; and the preparation method further comprises adding 0.05-0.1wt% ferrous sulfate (i.e. the final concentration of ferrous sulfate is 0.05-1wt%) to the sulfate-reducing bacteria solution. The amount of ferrous sulfate added specifically can be 0.05%, 0.08%, 1%, etc. The addition of ferrous sulfate can provide a substrate for sulfate-reducing bacteria to facilitate biological membrane formation. The source of the sulfate-reducing bacteria solution in the present application is not particularly limited, and commercially available sulfate-reducing bacteria can be used. The sulfate-reducing bacteria do not contain ferrous sulfate. In the embodiments of the present application, the sulfate-reducing bacteria solution specifically is Desulfovibrio The OD600 value (i.e. the absorbance at 600 nm is greater than or equal to 0.8) corresponds to the late logarithmic growth phase of the bacteria solution, at which time the bacterial activity is high and is suitable for use in membrane formation.

[0037] In some embodiments of the present application, the temperature of the biological membrane formation is 30-35℃, and can be 30℃, 32℃, 35℃, etc.; the time of the biological membrane formation is 7-10 days, and can be 7 days, 8 days, 10 days, etc. In the present application, after the biological membrane formation is successful, the surface of the filler ball will be obviously blackened, and the hand feeling is smooth and greasy.

[0038] In some embodiments of the present application, the temperature of the second drying is 30-40℃, and can be 30℃, 35℃, 40℃, etc.; the degree of the second drying is to reduce the water content to below 5 wt%, and can be 5 wt%, 4.5 wt%, 4 wt%, etc. In the present application, the heavy metal adsorption filler under the above drying conditions and degree can further ensure the activity of sulfate-reducing bacteria in the storage process; specifically, the second drying uses low-temperature drying, which is higher than the freezing point and lower than the critical temperature of protein denaturation and cell membrane damage. This temperature range can effectively promote water evaporation and enable the bacterial population to slowly dehydrate into a dormant state, rather than being killed by heat stress; and the water content below 5 wt% can greatly reduce the water activity in the system. In an extremely dry environment, the metabolism of the bacteria is basically stopped, and the energy and substances of the bacteria are maximally preserved, providing a physiological basis for long-term storage.

[0039] In the embodiments of the present application, the humidity of the second drying is <30%RH, and the time of the second drying is 24-48h, and can be 24h, 30h, 40h, 48h, etc. The above drying conditions can further reduce energy consumption and shorten the drying time.

[0040] The present application also provides a heavy metal adsorption filler prepared by the preparation method of any one of the above technical solutions.

[0041] The present application also provides the application of the heavy metal adsorption filler in the removal of heavy metals in underground water.

[0042] In some embodiments of the present application, the application includes soaking the heavy metal adsorption filler in an activation nutrient solution for 23-30h (specifically, 23h, 24h, 28h, 30h, etc.) for activation, and then placing it in an underground water remediation well for heavy metal removal.

[0043] In some embodiments of the present application, the activation nutrient solution is a mixed aqueous solution of sodium lactate, ammonium sulfate and potassium dihydrogen phosphate, wherein the concentration of sodium lactate is 0.8-1.2 g / L (specifically, 0.8 g / L, 1.0 g / L, 1.2 g / L, etc.), the concentration of ammonium sulfate is 0.15-0.25 g / L (specifically, 0.15 g / L, 0.20 g / L, 0.25 g / L, etc.), and the concentration of potassium dihydrogen phosphate is 0.03-0.07 g / L (specifically, 0.03 g / L, 0.05 g / L, 0.07 g / L, etc.).

[0044] The present application does not have special limitations on the amount of heavy metal adsorption filler used in the groundwater remediation well, which can be determined by those skilled in the art as needed.

[0045] The technical solutions in the present application will be described below in conjunction with examples. The examples of the present application are only used as examples, and all other examples obtained by those skilled in the art without creative labor are within the scope of protection of the present application.

[0046] Example 1 (1) 100 parts of wood chips passing through a 20-mesh sieve, 51 parts of attapulgite passing through a 100-mesh sieve, and 3 parts of sodium bicarbonate were mixed, then 34 parts of water was added, and the mixture was uniformly mixed in a blender to obtain a mud. The mud was fed into a roller-type ball press, and green balls with a diameter of 40 mm were pressed under a linear pressure of 4 kN / cm. The green balls were naturally air-dried for 48 h (after drying, the breakage rate of the green balls was 1.0% when they were dropped freely from a height of 0.5 m), and then loaded into an industrial kiln. The air excess coefficient ɑ was controlled at 0.9, and the pyrolysis was carried out at 550℃ for 5 h. After natural cooling, the filler balls were obtained.

[0047] (2) The filler balls were soaked in a bacterial solution to which 0.05 wt% ferrous sulfate had been added, and were incubated at 32℃ for 7 days. The filler was successfully colonized, was taken out and dried at 35℃ and humidity <30% RH for 36 h to obtain heavy metal adsorption filler with a water content of 4.5 wt%. The heavy metal adsorption filler was sealed and stored in an aluminum foil composite oxygen barrier bag. Desulfovibrio The bacterial solution was prepared as follows: 1 g / L of yeast extract, 0.5 g / L of beef extract, 0.5 g / L of peptone, 0.5 g / L of glucose, 0.5 g / L of sodium chloride, and 0.05 g / L of ferrous sulfate were dissolved in 100 mL of deionized water, and the pH was adjusted to 7.0 with 1 mol / L sodium hydroxide.

[0048] (3) After 7 days, the sealed bag was opened, and the heavy metal adsorption filler was placed in a nutrient solution (water as solvent) containing 1 g / L of sodium lactate, 0.2 g / L of ammonium sulfate, and 0.05 g / L of potassium dihydrogen phosphate, and was soaked for 24 h to obtain activated heavy metal adsorption filler.

[0049] A laboratory scale test system was constructed: a circular column with a diameter of 10 cm and a length of 50 cm was filled with 5 kg of activated heavy metal adsorption filler as a simulated remediation well, water was fed from the lower end and filtered water was simulated to flow out from the top end, the water inflow rate was set to 175 mL / min, the ion concentration in the water outflow of the simulated remediation well was determined, the simulated remediation well water contained cadmium 16.5 mg / L, zinc 2.5 mg / L, lead 4.5 mg / L, copper 2.5 mg / L, the specific composition was base electrolyte (calcium nitrate (Ca(NO3)2·4H2O, 50 mg / L), magnesium sulfate (MgSO4, 30 mg / L), potassium chloride (KCl, 10 mg / L)), sulfur source (sodium sulfate (Na2SO4, 100 mg / L)), phosphorus source (potassium dihydrogen phosphate (KH2PO4, 5 mg / L)), buffer salt (sodium bicarbonate (NaHCO3, 100 mg / L)), heavy metal pollutants (cadmium chloride (CdCl2, 26.9 mg / L), zinc sulfate (ZnSO4, 6.2 mg / L), lead nitrate (Pb(NO3)2, 7.2 mg / L), copper sulfate (CuSO4, 6.3 mg / L)), and the pH value was adjusted to 7.0 ± 0.2. The data results at 90 days of operation are shown in Table 1.

[0050] Example 2 The heavy metal adsorption filler was prepared and activated according to the method of Example 1 to obtain the activated heavy metal adsorption filler, and the only difference was that rice husk powder passing through a 20 mesh sieve was used instead of sawdust, and the breakage rate of 0.5 m high free falling was 1.25%.

[0051] The heavy metal removal effect of the obtained heavy metal adsorption filler was tested according to the test method in Example 1, and the only difference was that the water inflow rate was adjusted to 350 mL / min. The results are shown in Table 1.

[0052] Example 3 The heavy metal adsorption filler was prepared and activated according to the method of Example 1 to obtain the activated heavy metal adsorption filler, and the only difference was that the pyrolysis temperature was 600°C.

[0053] The heavy metal removal effect of the obtained heavy metal adsorption filler was tested according to the test method in Example 1, and the only difference was that the water inflow rate was adjusted to 750 mL / min. The data results at 90 days of operation are shown in Table 1.

[0054] Example 4 The heavy metal adsorption filler was prepared and activated according to the method of Example 1.

[0055] The groundwater of a certain mine land contains cadmium 16.4 mg / L, zinc 2.1 mg / L, lead 4.1 mg / L, and copper 2.2 mg / L. Three upstream and downstream remediation wells are arranged (vertically arranged side by side, respectively, perpendicular to the water flow direction), the upstream remediation well is a filler well, and the downstream remediation well is a sampling well, each on the corresponding groundwater contour line. The inlet diameter of the remediation well is 15 cm, and the water depth is 2 m. A screen pipe is arranged at the position of the remediation well corresponding to the aquifer, as a filler layer, filled with filler balls. The distance between the upstream remediation well and the downstream remediation well is 3 m, and the groundwater flow rate is 30 m / day. 15 kg of filler balls are filled in the upstream remediation well, and no filler is filled in the downstream remediation well. The liquid in the downstream remediation well is taken as the treated water, and the heavy metal content is detected. The data results after 90 days of operation are shown in Table 2.

[0056] Comparative Example 1 The heavy metal adsorption filler was prepared and activated according to the method of Example 1 to obtain the activated heavy metal adsorption filler, and the only difference was that the air excess coefficient was 1.5.

[0057] The heavy metal removal effect of the obtained heavy metal adsorption filler was tested by the test method in Example 1. The data results after 90 days of operation are shown in Table 1.

[0058] Comparative Example 2 The filler balls were prepared according to the method of step (1) of Example 1, without impregnating the bacterial solution, and the filler balls were directly used as heavy metal adsorption fillers for testing.

[0059] The heavy metal removal effect of the obtained heavy metal adsorption filler was tested by the test method in Example 1. The data results after 90 days of operation are shown in Table 1.

[0060] Table 1 Heavy metal removal effect of heavy metal adsorption fillers obtained in Examples 1-3 and Comparative Examples 1-2

[0061] Table 2 Heavy metal removal effect of heavy metal adsorption fillers in actual working conditions

[0062] As can be seen from Table 1, the heavy metal adsorption filler provided by the present application can effectively remove cadmium, zinc, lead, and copper heavy metals. As can be seen from the test results of Comparative Example 1, when pyrolysis is carried out under the condition of excessive air, i.e. high air excess coefficient, the adsorption performance of the obtained heavy metal adsorption material to heavy metals is significantly reduced. As can be seen from the test results of Comparative Example 2, when the filler balls are not loaded with bacteria, the adsorption performance of the obtained heavy metal adsorption material to heavy metals is significantly reduced. DesulfovibrioWhen the bacteria are removed, the removal effect of the heavy metals is obviously decreased. As shown in Table 2, the heavy metal adsorption filler provided by the present application can effectively remove cadmium, zinc, lead and copper heavy metals in the actual industrial and mining background. The cadmium, zinc, lead and copper concentrations of the water inlet of the upstream well are 16.5 ± 0.33, 2.5 ± 0.17, 4.5 ± 0.29 and 2.5 ± 0.17 mg / L, and the concentrations of the water outlet of the downstream well are 2.99 ± 0.09, 0.39 ± 0.02, 0.36 ± 0.02 and 0.29 ± 0.01 mg / L, and the heavy metal removal effect is stable. The heavy metal concentrations of the water inlet of the upstream well 1 and 3 are slightly lower than that of the upstream well 2, and the concentrations of the water outlet of the downstream well 1 and 3 are slightly lower than that of the downstream well 2, which indicates that there is groundwater mixing flow in the edge well, but the removal rates of the upstream well 2 to the above four heavy metals still reach 81.6%, 81.8%, 92.0% and 88.9%, which indicates that the filler provided by the present application has a good pollutant removal rate.

[0063] While the preferred embodiments of the application have been illustrated and described, it will be clear to those skilled in the art that various changes can be made without departing from the spirit and scope of the application as set forth in the appended claims.

Claims

1. A method for preparing a heavy metal adsorption filler, comprising the following steps: mixing biomass, palygorskite, a pore-forming agent and water, and compression molding to obtain green balls, sequentially performing first drying and anoxic pyrolysis on the green balls to obtain filler balls, soaking the filler balls in a sulfate-reducing bacteria solution, and sequentially performing biofilm formation and second drying to obtain a heavy metal adsorption filler. The biomass is at least one of straw powder, wood chips, rice husk powder and bamboo pole powder, and the particle size of the biomass is 20-40 mesh. The particle size of the palygorskite is 100-150 mesh. The pore-forming agent is at least one of sodium bicarbonate and calcium carbonate.

2. The production method according to claim 1, characterized by, The biomass is 100 parts, the palygorskite is 50-65 parts, the pore-forming agent is 3-8 parts, and the water is 30-40 parts by mass. The compression molding device is a roller-type ball press, and the linear specific pressure is 3-5 kN / cm.

3. The preparation method according to claim 1, characterized in that, The air process coefficient of the anoxic pyrolysis is less than 1, the temperature of the anoxic pyrolysis is 500-600℃, and the time of the anoxic pyrolysis is 4-6 h.

4. The production method according to any one of claims 1 to 3, characterized by, The absorbance of the sulfate-reducing bacteria solution at 600 nm is ≥0.

8. The method further comprises adding 0.05-0.1 wt% ferrous sulfate to the sulfate-reducing bacteria solution.

5. The production method according to claim 1, characterized by, The temperature of the biofilm formation is 30-35℃, and the time is 7-10 days.

6. The production method according to claim 1, characterized by, The temperature of the second drying is 30-40℃, and the degree of the second drying is to reduce the water content to less than 5 wt%. 8.A heavy metal adsorption filler obtained by the method of any one of claims 1-7. 9.Use of the heavy metal adsorption filler of claim 8 in the removal of heavy metals from underground water.

7. The production method according to claim 1, characterized by, The use comprises soaking the heavy metal adsorption filler in an activation nutrient solution for 23-30 h for activation, and then placing the heavy metal adsorption filler in an underground water remediation well for heavy metal removal. The activation nutrient solution is a mixed aqueous solution of sodium lactate, ammonium sulfate and potassium dihydrogen sulfate, wherein the concentration of sodium lactate is 0.8-1.2 g / L, the concentration of ammonium sulfate is 0.15-0.25 g / L, and the concentration of potassium dihydrogen phosphate is 0.03-0.07 g / L. ​ 10. Use according to claim 9, characterized in that, ​ ​

Citation Information

Patent Citations

  • Preparation method and application of immobilized sulfate reducing bacteria particles

    CN118652880A

  • Biochar-loaded nano iron-copper material for treating hexavalent chromium wastewater as well as preparation method and application of biochar-loaded nano iron-copper material

    CN119281296A

  • PRB filling material for groundwater pollution remediation and preparation method thereof

    CN119425613A

  • Method for repairing heavy metal polluted underground water based on slow-release repairing agent

    CN120328675A